2014
DOI: 10.1371/journal.pone.0113639
|View full text |Cite
|
Sign up to set email alerts
|

C3a Receptor Antagonist Ameliorates Inflammatory and Fibrotic Signals in Type 2 Diabetic Nephropathy by Suppressing the Activation of TGF-β/smad3 and IKBα Pathway

Abstract: ObjectiveDiabetic nephropathy (DN) is a serious complication for patients with diabetes mellitus (DM). Emerging evidence suggests that complement C3a is involved in the progression of DN. The aim of this study was to investigate the effect of C3a Receptor Agonist (C3aRA) on DN and its potential mechanism of action in rats with type 2 diabetes mellitus (T2DM).MethodsT2DM was induced in SD rats by a high fat diet (HFD) plus repeated low dose streptozocin (STZ) injections. T2DM rats were treated with vehicle or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 33 publications
2
53
0
1
Order By: Relevance
“…66 Moreover, extracellular membrane (ECM) protein activation and matrix degradation subdue is correlated with TGF-b-induced fibrogenesis. 67,68 Interestingly, TGF-b signal transduction is greatly connected with the Smads. 67,68 TGF-b on binding with two specific type I and type II serine/threonine kinase receptor convey its signal across the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Moreover, extracellular membrane (ECM) protein activation and matrix degradation subdue is correlated with TGF-b-induced fibrogenesis. 67,68 Interestingly, TGF-b signal transduction is greatly connected with the Smads. 67,68 TGF-b on binding with two specific type I and type II serine/threonine kinase receptor convey its signal across the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 Interestingly, TGF-b signal transduction is greatly connected with the Smads. 67,68 TGF-b on binding with two specific type I and type II serine/threonine kinase receptor convey its signal across the plasma membrane. Clinical study also showed elevated serum and urinary TGF-b1 level in DN patients.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue sections were analyzed with a Nikon A1Si confocal laser scanning microscope and NIS-Elements Advanced Research software, version 4.0 (Nikon, Tokyo), and S Plan Fluor ELWD 40ϫ DIC. The subsequent steps were carried out as described previously (64).…”
Section: Methodsmentioning
confidence: 99%
“…After confirming the RNA quality by agar gel electrophoresis, cDNA was synthesized. Real-time PCR was performed with the CFX96 TM real-time PCR detection system (Bio-Rad) using SYBR Premix Ex Taq TM (Tli RNase H Plus, Takara) as described previously (64). The gene encoding ␤-actin was used as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…TGFb1 is considered one of the most potent factors inducing glomerulosclerosis in the DN. 23,24 Clinical study showed that serum and urinary TGF-b1 was an important biochemical markers in DN patients. 25 It plays important role in the development of renal interstitial fibrosis mainly through the classical TGF-b1/Smads pathway-mediated renal tubular epithelial cell transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%